TEACHING SCHOOL CHILDREN THROUGH SONGS ANG PICTURES - Eshniyozova Jasmina Jo’rabekovna; Eshonqulova Sarvinoz Yashinovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:This article discusses the growing trend of incorporating songs and pictures  into  educational  practices  as  a  way  to  make  learning  more  engaging  and effective  for  students.  The  paper  emphasizes  the  significant  role  of  rhythm  and repetition in songs, which aids in memory retention and understanding. It explores how these methods benefit various subjects such as language acquisition, math, and science by appealing to different learning styles—auditory and visual. Songs not only help with vocabulary  acquisition  and  pronunciation  but  also  assist  in  teaching  numbers, sequences, and other factual information, making learning more enjoyable and less monotonous.  Additionally,  the  paper  highlights  the  emotional  impact  of  music, suggesting that songs can strengthen the connection between students and the material being taught. Ultimately, the integration of songs and pictures supports a more dynamic learning environment that fosters both engagement and retention.